Phenyl-functionalized diiron propanediselenolato complexes containing the chelated or bridged 1, 3-bis(diphenylphosphine)propane ligand. Issue 16 (17th September 2018) - Meng, Zhi-Fen; Gao, Hui-Ling; Wang, Jiu-Xia; Shang, Jing-Yan; Li, Chang-Gong
Abstract: Reaction of precursor Fe2 [( μ- SeCH2 )2 CHC6 H5 ](CO)6 (A ) with 1, 3-bis(diphenylphosphine)propane (dppp) in refluxing xylene yielded one diphosphine-containing complex Fe2 [( μ- SeCH2 )2 CHC6 H5 ](CO)4 ( κ 2 -dppp) (1 ) with the diphosphine of dppp displacing the apical and one basal carbonyl ligands of a single iron center, while treatment of precursorA with one-half equivalent of dppp in MeCN in the presence of Me3 NO·2H2 O gave another diphosphine-containing complex {Fe2 [( μ- SeCH2 )2 CHC6 H5 ](CO)5 }2 ( μ, κ 1, κ 1 -dppp) (2 ) with the diphosphine of the dppp bridging two diiron diselenolato clusters upon replacing one of basal carbonyls, respectively. The structures of both complexes were fully characterized by spectroscopic methods and X-ray crystallography. The electrochemical behaviors of both complexes were investigated by cyclic voltammetry (CV) and the electrochemical reduction of protons from acetic acid to give dihydrogen catalyzed by complex Fe2 [( μ- SeCH2 )2 CHC6 H5 ](CO)4 ( κ 2 -dppp) was observed. Graphical Abstract: